IMPLEMENTASI PENDIDIKAN KARAKTER TERINTEGRASI DALAM KEGIATAN PEMBELAJARAN PADA SMK JURUSAN BANGUNAN DI DAERAH ISTIMEWA YOGYAKARTA - Amad Jaedun; Eka Purwaningsih; Fistian Novita; M. Alwan Wiranata (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACTThe purposes of this research are to (1) identify the character values which are developed and integratedin the learning process, (2) reveal teachers’ learning strategy and its evaluation in integrating character values inthe learning process, and (3) identify the obstacels among vocational high school teachers of Building departmentin integrating character values.This study belongs to descriptive-evaluative research which was conducted through 8 state vocational highschools of Building department in Special Region of Yogyakarta. This research was under the umbrella theme from3 studies of the students of Civil Engineering Education and Planning Department, Faculty of Engineering UNY.The research participants were the teachers who taught the subjects of normative skills, vocational theory, andvocational practicum in Building Department of Vocational High Schools. Data collection techniques were usingquestionnaire, interview and documentation. Instrument validation was conducted by content validation. Dataanalysis technique was using descriptive analysis for both quantitative and qualitative method.The result of the research showed that (1) character values was developed differently through integrationthe learning process in the subjects of normative skills, vocational theory, and vocational practicum but most ofthem were not written in syllabus or lesson plan, (2) most of the learning strategies were generally conventionalones, which were not not written in syllabus or lesson plan as well as in the learning scenario, (3) the evaluationof character education was the weakest aspect from the implementation of integrated character education onlearning process because it had not conducted appropriately yet with the integrated character values, and (4) theteacher obstacles in implementing integrated character values were especially related to the teachers’ low abilityin designing, implementing, and evaluating the learning process of developed charKeywords: integrated learning of character values